Pengaruh Strategi Harga, Promosi dan Permintaan Pasar terhadap Profitabilitas UMKM di Kota Padang - Putra, Pramudita Syah; Rezki, Rahmat Zainul; Andrian, Danny; Al Haziz, Ahmad Sunafis; Zefriyenni, Zefriyenni (Jurnal Ecogen, 2025)
This study aims to determine the effect of pricing strategy, promotion and market demand consumer preferences on the Profitability of Micro, Small and Medium Enterprises (MSMEs). The unit of analysis is Micro, Small and Medium Enterprises (MSMEs) in Padang City. This study uses primary data obtained through questionnaires. The sampling technique uses quota sampling. A total of 100 questionnaires from MSMEs were returned as the final sample. The data were analyzed using multiple regression analysis conducted with SPSS software. The results showed that pricing strategy and promotion had a significant positive effect on profitability. While market demand had no significant effect on profitability. MSMEs need to set competitive prices and in accordance with the value perceived by consumers. MSMEs are advised to allocate a special budget for planned and measurable promotional activities.